2014
DOI: 10.1007/s12020-014-0348-1
|View full text |Cite
|
Sign up to set email alerts
|

Atrial conduction times and left atrium mechanical functions in patients with active acromegaly

Abstract: The aim of this study was to evaluate atrial electromechanical delay (EMD), P wave dispersion (Pwd), and left atrial (LA) mechanical functions in patients with active acromegaly. Twenty-three patients with active acromegaly and 27 age- and sex-matched controls were included in this study. All atrial electromechanical interval parameters (PA lateral, PA septum, PA tricuspid, interatrial EMD, intra-LA EMD, and intra-right atrial EMD) were measured from mitral lateral annulus, mitral septal annulus, and right ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 40 publications
0
17
1
2
Order By: Relevance
“…In a recent study, LA volumes (maximum, minimum, and presystolic) and LA mechanical functions were not significantly different in patients with active acromegaly compared with age‐ and gender‐matched healthy controls. Additionally, serum levels of GH and IGF‐1 did not correlate with LA mechanical functions . A previous animal study examined 11 cats with acromegaly; 6 of the subject animals had significantly enlarged LA .…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…In a recent study, LA volumes (maximum, minimum, and presystolic) and LA mechanical functions were not significantly different in patients with active acromegaly compared with age‐ and gender‐matched healthy controls. Additionally, serum levels of GH and IGF‐1 did not correlate with LA mechanical functions . A previous animal study examined 11 cats with acromegaly; 6 of the subject animals had significantly enlarged LA .…”
Section: Discussionmentioning
confidence: 84%
“…LVH and myocardial fibrosis are considered common findings in acromegalic cardiomyopathy in echocardiography studies . However, there is limited information on LA function in acromegaly …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An increased left atrial (LA) volume index is also known as a strong predictor of AF [3][4][5]. It has been reported that the intra-and interatrial conduction time, that is, the atrial electromechanical delay (AEMD), is an index of reflecting pathological changes of the atria [6][7][8][9][10][11][12][13]. AEMD can be measured not only by invasive electrophysiologic study but also by echocardiographic tissue Doppler imaging (TDI) [7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%